IMPROVING STUDENTS’ SPEAKING ACHIEVEMENT THROUGH THE APPLICATION OF SMALL GROUP DISCUSSION METHOD TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 21 MEDAN - Purba, Jelita; Rumapea, Linus; Sembiring, Novalina (Kairos English Language Teaching Journal, 2020)
This thesis discuss about Improving Students Speaking’ Achievement through the Application of Small Group Discussion Method to the Eighth Grade Students of SMP Negeri 21 Medan. The objective of the study was to find out how effective the use of Small Group Discussion Method (SGD) in teaching speaking especially in asking and giving opinion. The study of the research concentrates on the improving students’ speaking achievement by the application of small group discussion method. Specifically, it is concerned more about the students’ achievement in asking and giving opinion. The research has two cycles. Each cycle has three meetings. The subject of the research was students of Eighth grade students of SMP Negeri 21 Medan which consisted of twenty four students. The instruments of data collection were quantitative and qualitative data. While the quantitative data was conducted by pre-test, post-test I, and post-test II students’ speaking score in every cycle, the qualitative data conducted by the three instruments; observation sheet, questionnaire and diary notes. Based on the speaking tests, students’ score improved. In the pretest, the mean of the students was 48.82. The post-test I mean 68.66 and in the post-test II the mean of the students 77.91. Based on the observation sheet, questionnaire sheet and diary notes, it was found that learning activity ran well. Most students felt interested in the process of learning activity and involved in their group during the discussion time. The result of the research showed that Small Group Discussion Method was able to improve students’ achievement in asking and giving opinion.